MAFTIA Conceptual Model and Architecture - Adelsbach, A. (2001)
This document builds on the work reported in MAFTIA deliverable D1. It contains a refinement of the MAFTIA conceptual model and a discussion of the MAFTIA architecture. It also introduces the work done in WP6 on verification and assessment of security properties, which is reported on in more detail in MAFTIA deliverable D4